MOTIVATION INFLUENCING DECISION TO LEARN KOREAN LANGUAGE AMONG CHIANG MAI UNIVERSITY STUDENTS - SORNSUWANNASRI, Sayamon (International Journal of Korean Humanities and Social Sciences, 2020)
The objectives of this research are to investigate motivations that influence a decision to learn Korean language, and post-graduation expectations of 102 students studying Korean in Chiang Mai University. A questionnaire was conducted on the students’ motivation behind their decision to learn the Korean language and their expectations for Korean language learning after graduation. It was found that the type of motivation that has the highest influence over their Korean language learning is self-motivation, and they are also motivated by curriculum and institutes, the ‘Korean Wave’ and the society, defined as social motivation, respectively. Their highest post-graduation expectation for Korean language learning is the ability to converse fluently with Korean people, while the ability to understand Korean songs/dramas/variety programs, the ability to understand Korean society and culture, the ability to get a job using the Korean language, the opportunity to study in South Korea and the opportunity to have new friends are the next highest expectations successively.